Effect of TikTok-based health education on HIV/AIDS knowledge among vocational high school students - Fahrul Rozi; Annisaa Fitrah Umara; Imas Yoyoh (International Journal of Health Science and Technology, 2026)
In Indonesia, 35,415 new HIV cases were reported in 2024, with 6% occurring among individuals under 20 years of age. In Banten Province, 1,926 newly identified people living with HIV (PLHIV) initiated antiretroviral treatment in 2024. Adolescents' knowledge of HIV/AIDS is still very minimal, even though data is accessible through the internet and social media. This study aimed to examine the effect of TikTok-based short educational videos containing information on HIV transmission, prevention, symptoms, and misconceptions on vocational high school students' knowledge regarding HIV/AIDS. The method used was quantitative, using a pre-experimental design of one group pre-test and post-test. Students in grades X and XI, with a sample of 80 respondents, were selected using purposive sampling. Knowledge level questionnaire. The intervention was in the form of an HIV/AIDS education video uploaded to the TikTok account "hivawareid". Univariate and bivariate with Kolmogorov-Smirnov, analyzed with the Wilcoxon Signed Rank Test. The majority of respondents were aged 16–19 years (92.5%), and most were female (71.3%). The average knowledge score increased from 18.7 (pre-test) to 20.6 (post-test). The Wilcoxon Signed Rank Test showed a value of p = 0.001 (<0.05). There is a significant impact of health education through the social media platform TikTok on increasing adolescents' understanding of HIV and AIDS.